Fiscal policy and her roles in stimulating output growth in Cambodia: Bayesian inference based on BMA and MCMC simulation - Sean, Monorith; Yim, Chanmary (Journal of Management, Economics, and Industrial Organization, 2020)
This research paper aims to examine the impact of fiscal policy on Cambodia’s economic growth. More than that, this research also figures out fiscal stance on whether fiscal policy in Cambodia is contractionary or expansionary to stimulate the economy over the past two decades. Due to the limited observation, from 1994 through 2019, a totally of 26 years, this study employs Bayesian inference based on Bayesian Model Averaging (BMA) and Markov Chain Monte Carlo (MCMC) which uses Gibb Sampling to approximate posterior mean. By comparing these two approaches, the empirical results are identical. The empirical result revealed that Def, Debt, Faids, Er and Ex which represent government deficit, public debt, foreign aid, nominal exchange rate (KHR/USD) and export, respectively, are positive correlation with output growth in Cambodia. The increase in the deficit, public debt and foreign aid, means the government utilizes the fiscal policy to fine-tune the economy. Furthermore, this study also confirms that fiscal policy in Cambodia is conducted as a consolidated and stabilized policy. It can be concluded that the increase in the deficit, public debt, and foreign debt could stimulate the economy during the recession period where fiscal policy is acted as expansionary policy. During a post-recession, on the other hand, Royal Government of Cambodia (RGC) will conduct a contractionary fiscal policy to cool down the economy especially when the economy is overheating.